2023
DOI: 10.1007/s12192-022-01309-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular chaperone function of three small heat-shock proteins from a model probiotic species

Abstract: Small heat-shock proteins (sHSP) are ubiquitous ATP-independent chaperones that prevent irreversible aggregation of heat-damaged denaturing proteins. Lactiplantibacillus plantarum is a widespread Gram-positive bacterium with probiotic claims and vast potential for agro-food, biotechnological and biomedical applications. L. plantarum possesses a family of three sHSP, which were previously demonstrated to be involved in its stress tolerance mechanisms. Here, the three L. plantarum sHSP were heterologously expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
3
0
1
Order By: Relevance
“…Stress proteins such as small heat shock proteins (sHSP) are present in almost all organisms. Although they have all been described for their role as molecular chaperones 7 , 27 29 , a growing number of studies have shown that some of them also play the role of lipochaperon by acting at the cell membrane level to maintain its integrity 16 , 20 24 , 30 – 32 . Few sHSPs have been described as performing both these activities, the mechanisms involved in lipochaperon activity are still very poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress proteins such as small heat shock proteins (sHSP) are present in almost all organisms. Although they have all been described for their role as molecular chaperones 7 , 27 29 , a growing number of studies have shown that some of them also play the role of lipochaperon by acting at the cell membrane level to maintain its integrity 16 , 20 24 , 30 – 32 . Few sHSPs have been described as performing both these activities, the mechanisms involved in lipochaperon activity are still very poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 , HSP17 from Synechocystis sp . 16 , 17 , HSP17.8 from Arabidopsis thaliana 18 HSP15.8 and HSP16 from Schizosaccharomyces pombe 19 and HSP18.55 from Lactiplantibacillus plantarum 20 have been described as possessing this second activity.…”
Section: Introductionmentioning
confidence: 99%
“…The three sHSP modulated liposome membrane fluidity differently, with a clear lipochaperone activity for sHSP2. The different apparent functions of the three sHSPs of L. plantarum may account for the organism’s high adaptability and capacity to tolerate various stress conditions (Rocchetti et al 2023 ).…”
Section: Studying the Function Of Shspsmentioning
confidence: 99%
“…Su estructura se caracteriza por un bajo peso molecular (12-43 kDa) y la presencia de un dominio central de α-cristalina altamente conservado (aproximadamente 100 aminoácidos aminoácidos), sus propiedades chaperonas parecen estar estrechamente relacionadas con su capacidad para formar estructuras cuaternarias oligoméricas de diferentes tamaños que encierran el sustrato desplegado, lo protegen del entorno externo y de la agregación/precipitación [Rocchetti et al, 2022].…”
Section: Proteínas De Choque Térmicounclassified